PROFIL SOSIAL EKONOMI DAN EKOLOGI TIGA KOMUNITAS TRANSMIGRASI DI KAWASAN TOLIWANG HALMAHERA UTARA PASCA KONFLlK - Widiono, Septri (Jurnal AGRISEP, 2004)
The article describes community map by using socio-economic and ecological profile method in three communities at  Toliwang, Halmahera Utara post-conflict. Based on the research, it  was concluded that ecological capital have main potentially while social, money, physical and human capital need strengthening by assistance. The running of community empowerment has to be based on  participatory  and  sustainability  principal  so that  the  conflict  potential  sources  should  be considered. They involve local power relation, ethnic and'religion  different, institutional aspect, and land tenure.